Influence of Iron Catalyst in the Carbon Spheres Synthesis for Energy and Electrochemical Applications. Issue 16 (14th May 2018) - Scarselli, Manuela; Limosani, Francesca; Passacantando, Maurizio; D'Orazio, Franco; Nardone, Michele; Cacciotti, Ilaria; Arduini, Fabiana; Gautron, Eric; De Crescenzi, Maurizio
Abstract: Carbon spheres of nanometric dimension are known since the first studies on the synthesis of fullerenes. Their shape originates from the curvature of a carbon sheet similar to fullerenes, but with numerous graphitic rings that regulate the inside structure and the formation of open edges at the surface. This paper focuses on the structural and electronic characterization of carbon spheres obtained from a chemical vapor deposition synthesis process. Two different sets of samples are analyzed in detail, in particular, electron microscopies and Raman spectroscopy help understanding the morphology and the graphitic‐sp 2 arrangement of the carbon atoms in the architectures. In addition, the iron catalyst used during the reaction process confers the carbon spheres a ferromagnetic response at room temperature. Therefore, both the structural properties of the samples and the active contribution of iron mark the difference in the measured photoresponse as well as in the electrochemical behavior. The X‐ray photoelectron spectroscopy study addresses these points by giving information on the composition and the iron chemical state in the assembly. The collected results underline the advantages offered by this nanomaterial for sustainable applications. Abstract : The paper describes a synthesis method to obtain carbon nanospheres. The structural features of the spheres and the active contribution of the iron catalyst mark the difference in their photoresponse as well as in the electrochemical performance. The reported results demonstrate that the presence of residual iron inside the spheres is not detrimental for some targeted applications.